Unmanned aerial system applications in construction: a systematic review. Issue 4 (18th October 2018) - Zhou, Shi; Gheisari, Masoud
Abstract : Purpose: Over the past decade, researchers have used unmanned aerial systems (UASs) in construction industry for various applications from site inspection to safety monitoring or building maintenance. This paper aims to assort academic studies on construction UAS applications, summarize logics behind using UAS in each application and extend understanding of current state of UAS research in the construction setting. Design/methodology/approach: This research follows a systematic literature assessment methodology to summarize the results of 54 research papers over the past ten years and outlines the research trends for applying UASs in construction. Findings: UASs are used in building inspection, damage assessment, site surveying, safety inspection, progress monitoring, building maintenance and other construction applications. Cost saving, time efficiency and improved accessibility are the primary reasons for choosing UAS in construction applications. Rotary-wing UASs are the most common types of UASs being used in construction. Cameras, LiDAR and Kinect are the most common onboard sensors integrated in construction UAS applications. The control styles used are manual, semi-autonomous and autonomous. Originality/value: This paper contributes to classification of UAS applications in construction research and identification of UAS hardware and sensor types as well as their flying control systems in construction literature.